2018
DOI: 10.3390/biom8020015
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis Clathrin Assembly Protein with a Predicted Role in Plant Defense Can Function as an Adenylate Cyclase

Abstract: Adenylate cyclases (ACs), much like guanylate cyclases (GCs), are increasingly recognized as essential parts of many plant processes including biotic and abiotic stress responses. In order to identify novel ACs, we have applied a search motif derived from experimentally tested GCs and identified a number of Arabidopsis thaliana candidates including a clathrin assembly protein (AT1G68110; AtClAP). AtClAP contains a catalytic centre that can complement the AC-deficient mutant cyaA in E. coli, and a recombinant A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 43 publications
3
45
0
3
Order By: Relevance
“…Assmann, 1995;Gehring, 2010) further supporting the role of cAMP in plant signaling cascades. However, to-date only few ACs have been experimentally tested in higher plants; these include a Zea mays protein that participates in polarized pollen tube growth (Moutinho et al, 2001), a Nicotiana benthamiana protein with a role in tabtoxinine-β-lactam-induced cell death (Ito, 2014), a Hippeastrum x hybridum protein that is involved in stress signaling (Świeżawska et al, 2014), an Arabidopsis pentatricopeptide repeat-containing protein, AtPPR (At1g62590) (Ruzvidzo et al, 2013), an Arabidopsis clathrin assembly protein with a predicted role in actin cytoskeletal remodeling during endocytic internalization (Chatukuta et al, 2018) and an Arabidopsis K + -uptake permease (KT/HAK/KUP7; AtKUP7, At5g09400; Al-Younis et al, 2015). One possible reason for this apparent elusiveness is the evolutionary divergence of plant nucleotide cyclases where only key amino acids within the catalytic centers appear to be retained.…”
Section: Introductionmentioning
confidence: 99%
“…Assmann, 1995;Gehring, 2010) further supporting the role of cAMP in plant signaling cascades. However, to-date only few ACs have been experimentally tested in higher plants; these include a Zea mays protein that participates in polarized pollen tube growth (Moutinho et al, 2001), a Nicotiana benthamiana protein with a role in tabtoxinine-β-lactam-induced cell death (Ito, 2014), a Hippeastrum x hybridum protein that is involved in stress signaling (Świeżawska et al, 2014), an Arabidopsis pentatricopeptide repeat-containing protein, AtPPR (At1g62590) (Ruzvidzo et al, 2013), an Arabidopsis clathrin assembly protein with a predicted role in actin cytoskeletal remodeling during endocytic internalization (Chatukuta et al, 2018) and an Arabidopsis K + -uptake permease (KT/HAK/KUP7; AtKUP7, At5g09400; Al-Younis et al, 2015). One possible reason for this apparent elusiveness is the evolutionary divergence of plant nucleotide cyclases where only key amino acids within the catalytic centers appear to be retained.…”
Section: Introductionmentioning
confidence: 99%
“…The average human AC activity was $ 40 pmol cAMP mg À1 protein min À1 [29], while kidney-specific rat AC activity was 145 pmol cAMP mg À1 protein min À1 [30]; bacterial photoactivated cyclase bPAC from Beggiatoa sp produced~10 nm cAMP mg À1 protein min À1 [31]. Based on the obtained results and the available literature, it can be concluded that cAMP synthesis is not the main function of plant proteins with AC domains [27,28].…”
Section: Purification Of Bdttm3 Recombinant Protein and In Vitro Enzymentioning
confidence: 88%
“…It is worth pointing out that the AC activity of BdTTM3 is~1100 times lower than its activity in catalyzing the decomposition of ATP into ADP and a free phosphate. The cAMP level produced by other proteins with AC activity from A. thaliana was 2.2 pmol protein -1 Ámin -1 for AtKUP7 [27] and 7.3 pmol protein -1 Ámin -1 for AtClAP [28]. However, for AtTTM1, AtTTM2, and AtTTM3, no cyclase activity was determined [8].…”
Section: Purification Of Bdttm3 Recombinant Protein and In Vitro Enzymentioning
confidence: 99%
“…При этом в формировании цАМФ могут участвовать мембранные и цитоплазматические аденилатциклазы растений [46]. Биоинформационный анализ показывает, что у растений специфичные для аденилатциклаз мотивы могут присутствовать в составе других белков [47]. Например, пять растительных белков у арабидопсиса обладают такими мотивами, среди них мембранный белок AtKUP7, ответственный за транспорт калия в клетку.…”
Section: механизмы передачи сигнала от гетеротримерного G-белка к внуunclassified
“…Например, пять растительных белков у арабидопсиса обладают такими мотивами, среди них мембранный белок AtKUP7, ответственный за транспорт калия в клетку. У кукурузы выявлен белок ZmPSiP, регулирующий прорастание пыльцевой трубки [47], а также некоторые другие белки. Аналогичную ситуацию наблюдали и с ферментами, синтезирующими цГМФ -гуанилатциклазами [48].…”
Section: механизмы передачи сигнала от гетеротримерного G-белка к внуunclassified